Network Discretization for Transient Flow Analysis - J. Twyman (Ingeniería del Agua)
When applying the method of characteristics in the transient analysis, the pipe network should be discretized in such a way as to avoid the appearance of errors due to the non- compliance of the Courant condition, which can be difficult to achieve since the systems are generally composed by pipes which are diverse in terms of their physical characteristics (length, constituent material, etc.). To solve this there are techniques such as the method of the wave speed adjustment (MWSA) which, despite being an easy method to apply, must comply with several conditions difficult to verify, even in very simple systems. When analyzing a more complex system, it is concluded that the process of eliminating the conflicting pipes or replacing them with fictitious pipes allows obtaining a solution close to the exact one without the need to apply the MWSA, this at low execution times and without affecting noticeably the results quality.